Structural enablements and constraints in the creation and enactment of local content in Norwegian education - Rød, Daniel Andre Voll; Bæck, Unn-Doris K. (Nordic Journal of Studies in Educational Policy, 2020)
In Norway, the national curriculum together with the Education Act serves as the foundation for teaching and learning in primary and secondary education and training. Local educational providers are given autonomy to develop local adaptations of the centrally given subject-specific curriculum competence aims. This article explores some structural enablements and constraints tied to teachers’ opportunities to make use of local content in curricula in lower secondary schools in Norway, including rural/urban differences. The analysis is based on data consisting of 18 qualitative interviews with teachers in two municipalities and participant observation in one of the municipalities in Northern Norway. The finding of this paper is that the design of the national curriculum allows for local content based on its competence aims. This serves as an enabler for teachers to create and enact local content in education. However, there are several constraints that limit local adaptation for teachers – time pressure, lack of access to content due to finances and distance and losing school control of local curriculum. Also, these constraints have a different impact depending on the geographical context. The article employs Margaret Archer’s theories on centralized and decentralized educational systems to analyse these structural enablements and constraints.